2005
DOI: 10.1002/elps.200410277
|View full text |Cite
|
Sign up to set email alerts
|

Piperazine-based buffers for liposome coating of capillaries for electrophoresis

Abstract: Anionic liposomes can be coated on fused-silica capillaries for electrophoresis in the presence of N-(hydroxyethyl)piperazine-N'-(2-ethanesulfonic acid) (HEPES) as background electrolyte (BGE) solution. In this work, the interaction of various compounds with zwitterionic and anionic phospholipid coatings was studied with HEPES at pH 7.4 as BGE solution. The chromatographic and electrophoretic behavior of three test sample solutions (anionic, cationic, and neutral) was investigated for evaluation of the phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…1). In the previous studies, HEPES and other piperazine-based buffers have been found superior to other organic and inorganic buffer ions as BGEs [42,43]. Here, the stability of the POPC/DSPEG3000 coating was investigated at varying pH conditions in the presence of HEPES or, alternatively, inorganic borate buffer.…”
Section: Effect Of Popc/dspeg3000 Coating On Surface Chargementioning
confidence: 96%
“…1). In the previous studies, HEPES and other piperazine-based buffers have been found superior to other organic and inorganic buffer ions as BGEs [42,43]. Here, the stability of the POPC/DSPEG3000 coating was investigated at varying pH conditions in the presence of HEPES or, alternatively, inorganic borate buffer.…”
Section: Effect Of Popc/dspeg3000 Coating On Surface Chargementioning
confidence: 96%
“…(2) for systems containing liposomes. Some buffer compositions may enhance the adsorption of liposomes to the fused silica capillary wall [27], however, phosphate buffers are known to minimize such adsorption [28] and therefore it was selected as the buffer compound for this study. The retention factors of the selected wastewater compounds in the presence of liposomes are shown in Fig.…”
Section: Separation Of the Model Compounds By Liposome Electrokineticmentioning
confidence: 99%
“…However, in most cases they exhibit electric charges. For this reason, they can be analyzed by CE, and they proved useful as anionic pseudostationary phases in EKC ( ; for recent reviews see [23,24]. It was found that, besides the pH, the kind of the electrolytes [6,25] and its ionic strength [5,18], and the preparation procedure of the vesicles influences the electrophoretic properties of the particles [23,26].…”
Section: Introductionmentioning
confidence: 98%